Thermophysical Analysis and Modeling of the Crystallization and Melting Behavior of Pla with Talc: Kinetics and Crystalline Structures - Siginer, D (Springer Netherlands, 2017)
The crystallization kinetics and the melting behavior of PLA and PLA with talc are investigated by dynamic scanning calorimeter and optical microscopy. The polymorphic aspect of PLA was highlighted by analyzing the melting process throughout heating after isothermal crystallization. The melting process of PLA with 5 mass% talc (PLAT5) shows the same thermal transitions as for PLA alone. The thermodynamic melting temperature of PLA and PLAT5 is determined to be 167.7 °C. The effects of the temperature and the cooling rate on the crystallization kinetics of PLA are analyzed. Finally, a simple and efficient protocol is defined to model the isothermal and the non-isothermal crystallization taking into account the polymorphism of PLA. Good agreement is found between the predictions of the proposed model and the experimental results under isothermal and non-isothermal conditions. © 2016, Akadémiai Kiadó, Budapest, Hungary.